Silicon RC-Snubber for 900 V Applications Utilising non-Stoichiometric Silicon Nitride - Boettcher, N.; Heckel, T.; Erlbacher, Tobias; Pelaic, Katja (31st International Symposium on Power Semiconductor Devices & ICs, 2019)
This paper presents a novel approach for the realisation of silicon RC-snubbers suitable for 900 V applications. The fabrication of dielectric layers with a thickness feasible for this voltage class poses challenges in terms of mechanical stress management, which have not been overcome by other approaches so far. The presented technology focuses on stress reduction during fabrication by utilisation of non-stoichiometric silicon nitride. A wide case study is performed in order to characterise dielectriclayer stacks including non-stoichiometric silicon nitride withrespect to manufacturability and electric properties. By keepingthe amount of non-stoichiometric silicon nitride in dielectric layerstack small, silicon RC-snubbers exhibiting dielectric strength of more than 1500 V and leakage current of less than 100 nA at 900 V can be fabricated. The feasibility for 900 V switching application is demonstrated in a double-pulse experimen
CRIS-Team WoS Importer:2019-09-27